Microcontroller-based fertigation farming automation system - Baharudin Zamani, Zarina; Anuar, Nor Shafarina; Mohamad, A.Nasoruddin; Anuar, Aina Safiqa; Sabirullah, Nor Azura (UPSI Press, 2022)
Fertigation is a technique that combines plant fertigation and irrigation that becomes most used by the commercial farmers as well as home growers. However, fertigation systems required a constant water supply and the exact amount of nutrient that plant needed as it changes depending on their growth. The paper aims to research, create, built, test and implement an automatic mixing fertilizer by implementing Total Dissolved Solids (TDS) monitoring system according to the plant’s nutrient level needed. It is also exploring the potential of optimum water usage by constructing an automatic timer for watering the plants according to the routine schedule. The system used an Arduino UNO R3 as a microcontroller. TDS sensor sense and measure the dissolved solids in a nutrient solution which gives information on the number of nutrients or impurities in TDS value. In an automatic watering system, the pump is running according to the timer set by a microcontroller. The frequency of distribution and the concentration of the solution depends on the weather conditions and the level of the crop. Hot weather requires more amount and frequency of fertilizer but in dilute solution. As such, this system has demonstrated a cost-effective, sustainable, eco-friendly, and safe environment as a result it will produce fresh and healthy plants that can give benefits to living things.